Ordered arrays of metal nanostructures on insulator/metal film: dependence of plasmonic properties on lattice orientation - Eugene Bortchagovsky; Fang Dai; Jia Tang; Ralfy Kenaz; Ilya Milekhin; Yurii Demydenko; Alla Bogoslovska; Pierre-Michel Adam; Ronen Rapaport; Monika Fleischer; Dietrich R T Zahn (Nano Express)
We study the dependence of the optical response of square lattices of plasmonic nanoparticles on the mutual orientation of the lattice and the plane of incidence of illuminating light. It is shown that the lattice sums for two orientations of the plane of incidence—along the rows of the squares and along their diagonal—are different. The presented micro-ellipsometric spectra confirm that different lattice sums and different conditions for the excitation of surface plasmons in the substrate at different orientations result in a distinct dispersion of the observed modes.